2013
DOI: 10.1182/blood-2012-07-444026
|View full text |Cite
|
Sign up to set email alerts
|

Promoting regulation via the inhibition of DNAM-1 after transplantation

Abstract: Key Points• The DNAM-1 adhesion and costimulatory pathway promotes GVHD via effects on regulatory T cells.• Effective GVL can still occur in the absence of DNAM-1, making the pathway an attractive therapeutic target.Donor T cells play pivotal roles in graft-versus-host disease (GVHD) and graft-versusleukemia (GVL) effects following bone marrow transplantation (BMT). DNAX accessory molecule 1 (DNAM-1) is a costimulatory and adhesion molecule, expressed mainly by natural killer cells and CD8 1 T cells at steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 47 publications
4
27
0
Order By: Relevance
“…In addition to the molecules associated with Treg survival mentioned in the results, G-CSF significantly upregulated molecules known to be involved in pathways that regulate T cell function including neuropilin-1 (29), Hdac4 (30), Bcl6 (31), Jak1 (32), CD83 (33), Atg2a (34), Tgfb1 (35), chd4 (36), ccr5 (37). Similarly, DNAM-1 (38), pim1 (39), IER3 (40) and IL10 were down regulated, the latter consistent with the finding here that natural regulatory T cells do not need to make IL-10 themselves for effective function. Together, these data confirm profound transcriptional regulation by G-CSF, an effect that our data suggests may at least in part mediated by direct receptor ligation.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to the molecules associated with Treg survival mentioned in the results, G-CSF significantly upregulated molecules known to be involved in pathways that regulate T cell function including neuropilin-1 (29), Hdac4 (30), Bcl6 (31), Jak1 (32), CD83 (33), Atg2a (34), Tgfb1 (35), chd4 (36), ccr5 (37). Similarly, DNAM-1 (38), pim1 (39), IER3 (40) and IL10 were down regulated, the latter consistent with the finding here that natural regulatory T cells do not need to make IL-10 themselves for effective function. Together, these data confirm profound transcriptional regulation by G-CSF, an effect that our data suggests may at least in part mediated by direct receptor ligation.…”
Section: Discussionsupporting
confidence: 87%
“…Although NK cells have long been of interest in GVHD (24, 25), NK cells of donor origin, which reduce GVHD while enhancing graft anti-tumor activity (2633), are the most well-studied. With regard to recipient NK cells, a recent study suggested that recipient NK cells control proliferation of antigen-stimulated donor T cells by a perforin-independent, Fas-dependent mechanism (16).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, B6 into BALB/c and B6 into bm1 GVHD models were used as CD4-and CD8-dependent models, respectively. 27 Weight curves and mortality rates in BALB/c mice administered dnRARa-CD4 Cre CD4…”
Section: Blood 19 September 2013 X Volume 122 Number 12 Vitamin a Mmentioning
confidence: 99%